Macular Ganglion Cell and Inner Plexiform Layer Thickness Is More Strongly Associated With Visual Function in Multiple Sclerosis Than Bruch Membrane Opening–Minimum Rim Width or Peripapillary Retinal Nerve Fiber Layer Thicknesses. Issue 4 (December 2019) - Nguyen, James; Rothman, Alissa; Gonzalez, Natalia; Avornu, Ama; Ogbuokiri, Esther; Balcer, Laura J.; Galetta, Steven L.; Frohman, Elliot M.; Frohman, Teresa; Crainiceanu, Ciprian; Calabresi, Peter A.; Saidha, Shiv
Abstract : Background: Optical coherence tomography (OCT) measurements of ganglion cell + inner plexiform layer (GCIPL) and peripapillary retinal nerve fiber layer (pRNFL) thicknesses are associated with visual function (VF) and disability in multiple sclerosis (MS). However, the value of measuring Bruch membrane opening–minimum rim width (BMO-MRW) thickness in MS remains unclear. Methods: Sixty-eight patients with MS and 22 healthy controls (HCs) underwent spectral domain OCT, 100%-contrast visual acuity (VA), 2.5%- and 1.25%-contrast letter acuity (LA), and Expanded Disability Status Scale (EDSS) testing. Mixed-effects linear regression models, accounting for within-subject, intereye correlations, were used to assess relationships. Results: The MS cohort exhibited significantly lower BMO-MRW ( P = 0.01), pRNFL at 3.7-, 4.1-, and 4.7-mm diameters surrounding the optic disc ( P < 0.001 for all), and GCIPL ( P < 0.001) thicknesses than HCs. BMO-MRW thickness was associated with 100%-VA ( P < 0.001, R 2 = 0.08), 2.5%-LA ( P < 0.001; R 2 = 0.13), and 1.25%-LA ( P = 0.002; R 2 = 0.11). All measured pRNFL thicknesses were associated with high- and low-contrast VF (all: P < 0.001). GCIPL thickness was more strongly associated with 100%-VA ( P < 0.001; R 2 = 0.23), 2.5%-LA ( P < 0.001; R 2 = 0.27), and 1.25%-LA ( P < 0.001; R 2 = 0.21) than the other OCT measures assessed. All OCT measures were significantly, but weakly, associated with EDSS scores. Conclusions: BMO-MRW and pRNFL thicknesses are reduced and associated with VF and disability in MS, but GCIPL thickness is a stronger marker of visual impairment. Our findings corroborate the utility of OCT in providing valuable information regarding the MS disease process.